Combination of Span 20 and pH-assisted walnut oil extraction during aqueous extraction process. (May 2018) - Chen, Jia; Yu, Xiuzhu; Geng, Qiaona; Li, Mengjun
Abstract: To destabilize the emulsion during aqueous extraction processing (AEP) and improve oil yield of walnuts, sugar-aided aqueous extraction (SAAE) with optimized extraction parameters was explored. Demulsification mechanism using Span 20 at acidic pH during SAAE was discovered. Highest walnut oil yield (90.74%) was obtained at sugar solution of 1 mol/L, solvent-to-sample ratio of 4:1, and extraction temperature of 85 °C, extraction time of 60 min, 1.9 g/100 g Span 20, and pH 6.0. Span 20 significantly improved walnut oil yield by allowing the release of oil and decreasing the emulsion fraction. This result may have been caused by the dominance of Span 20 at the interface, resulting in unstable emulsions. No evident change was found in the walnut protein, suggesting that the obtained protein can be reclaimed. Highlights: The proposed method achieved high oil yield (90.74%). Extraction time was reduced by the proposed method. Proteins recovery was intact during SAAE. The effect of Span20 was proved by microscopic and droplet size analysis. Sugar solution could be reused.